The ambivalence of santiago a psychoanalytic study - S. Sujatha, T (International Journal of Engineering and Technology, 2017)
Santiago, the protagonist of the American novelist, Ernest Hemingway’s novella, The Old Man and the Sea is certainly a sphinx amongst complex characters in fictional literature. A true understanding of this very puzzling character is beyond the scope of the conventional study methods of critical reading, critical analysis, critical appreciation etc. Only a psychoanalytic approach offers us some prospect of being able to understand the dichotomy between the psyche and the persona of Santiago. However, it needs to be emphasized here that the psychoanalytic approach is neither superior nor inferior to the other approaches. It is only a very different kind of approach that promises new possibilities. Its application is justified when our subject of study happens to be a complex character like Santiago. We also need to remain alert and wary of the fact that a pseudo-psychoanalytic study can easily lead to absurd understandings. This paper reports a study of Santiago’s character based specifically on Freudian Classical Psychoanalytic Theory of Personality. At the same time, however, it does not altogether disregard or discount Jungian or Lacanian psychoanalyses. The objective of this paper is to explain in psychoanalytic terms how Santiago is saved from becoming dangerously paranoid, schizoid and maniacal.